PENGARUH INDEPENDENSI, KOMPLEKSITAS TUGAS, DAN GENDER TERHADAP AUDIT JUDGMENT - Rossa Komalasari; Erna Hernawati (Neo-Bis, 2015)
This study aims to empirically examine the influence of independence, task complexity and gender on audit judgment. The sample of this study is the auditor who worked on KAP in DKI Jakarta. Samples was done by cluster sampling method. Data was collected through questionnaire distributed directly to the auditor as many as 100 and only 80 questionnaires can be used. Data were analyzed using multiple linear regression method were processed with SPSS 20.0. the result of this study indicate that independence and task complexity of the audit has a significant impact on audit judgment, while the gender had no significant effect on audit judgment